2019
DOI: 10.1055/s-0039-1695026
|View full text |Cite
|
Sign up to set email alerts
|

Lateral-Expansion Pharyngoplasty: Combined Technique for the Treatment of Obstructive Sleep Apnea Syndrome

Abstract: Introduction  Obstructive sleep apnea syndrome (OSAS) is a multifactorial disease characterized by episodes of partial or complete collapse during sleep of different regions of the upper airway. Surgery for OSAS evolved with the introduction of different techniques, considering new surgical concept of reconstruction of the upper airway. Objective  To retrospectively evaluate the effectiveness of a new approach aimed at reducing pharyngeal collapse by combining two surgical techniques: lateral and expansion ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The majority of samples included in the study consisted of patients affected by severe OSAS (mean pre-op apnea–hypopnea index (AHI) > 30). A mean reduction of more than 50% of AHI and a mean post-op AHI < 20 were observed in all series except one [ 10 ]. Some authors did not specify complications and their rates.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of samples included in the study consisted of patients affected by severe OSAS (mean pre-op apnea–hypopnea index (AHI) > 30). A mean reduction of more than 50% of AHI and a mean post-op AHI < 20 were observed in all series except one [ 10 ]. Some authors did not specify complications and their rates.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the possible swallowing complication presented by LP, other authors consider SPC a successful target. José Antonio Pinto et al [ 10 ], in so-called lateral-expansion pharyngoplasty, suggested the association of LP with expansion sphincter pharyngoplasty, presented for the first time by Pang and Woodson. In this way, the SPC section is combined with the section of PP muscle and the further suture of its cranial flap to the hamulus of the pterygoid process in order to improve the retropalatal obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Patient selection and choice of surgical procedure for OSA have traditionally relied on static examination of the awake patient, and thus may not accurately predict sites of obstruction during the sleeping state [15,16,18,19]. Awake upper airway endoscopy can be done safely in the office setting and it is useful for evaluating any anatomic variants of the upper airway structures such as deviated nasal septum, turbinate hypertrophy, and adenotonsillar hypertrophy as well as for ruling out pathological obstruction such as nasal polyps and tumors [15,16,[20][21][22][23][24][25][26][27][28][29][30]. Tonsil grade, Friedman palate position, and Friedman lingual tonsil grade have been considered useful scores for identifying patients in whom single-level velopharyngeal surgery should be avoided [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, as indicated in the European position paper on drug-induced sleep endoscopy [19], DISE could be useful for guiding clinicians in the choice of the best surgical treatment. If during DISE only a velar and oropharyngeal obstruction is identified, a single-level pharyngoplasty surgery is usually indicated [20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…Abdullah Alhelali Otolaryngology Department, Aseer Central Hospital, Abha, Saudi Arabia *Address all correspondence to: alhelaliii@hotmail.com proposed [51][52][53]. Many noncomparative studies reported its success in treating OSAS [54,55]. One systematic review with a meta-analysis showed a significantly better EPP result than other traditional surgeries [56].…”
Section: Author Detailsmentioning
confidence: 99%